2021
DOI: 10.1088/1755-1315/733/1/012118
|View full text |Cite
|
Sign up to set email alerts
|

Good manufacturing practices for risk management in food safety sustainability: An empirical study

Abstract: Food is an essential need for the sustainability of human life so that consumers have the right to get a product that is safe for consumption. However, food poisoning cases due to the risk of biological, chemical, physical, and other contamination still occur frequently. In this study, an empirical investigation was conducted on apple pie production in a food processing SME that is known to have a risk of physical, chemical, and biological. This study used the hazard analysis and critical control point (HACCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Huysentruyt et al [22] presented an application of GAMP 5 for AI-based systems. In recent work, Andriani et al [23] reported a case study of a GAMP application to analyse and prioritise risks in the production process. Suseno et al [24] emphasised knowledge sharing and GMP performance.…”
Section: Validation Of Process Control Systems Of Automated Manufactu...mentioning
confidence: 99%
“…Huysentruyt et al [22] presented an application of GAMP 5 for AI-based systems. In recent work, Andriani et al [23] reported a case study of a GAMP application to analyse and prioritise risks in the production process. Suseno et al [24] emphasised knowledge sharing and GMP performance.…”
Section: Validation Of Process Control Systems Of Automated Manufactu...mentioning
confidence: 99%